MOF-199 derived carbon-montmorillonite composite material as well as preparation method and application thereof

By combining MOF-199 with montmorillonite, carbonization and plasma treatment, MOF-199-derived carbon @ montmorillonite composites were prepared, which solved the problem of limited adsorption capacity of existing MOF materials in low concentration environments of VOCs, and achieved efficient adsorption and good renewable performance.

CN119701893APending Publication Date: 2025-03-28ZINGKE (CHONGQING) ADVANCED MATERIALS RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411902163.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing MOF materials have limited adsorption capacity in low concentration environments of VOCs and cannot effectively adsorb VOCs.

Method used

By combining MOF-199 with montmorillonite, carbonization and plasma treatment were performed, MOF-199-derived carbon@montmorillonite composite material was prepared. This material improves the adsorption capacity of VOCs through the structure of porous carbon pillared montmorillonite, combining electrostatic adsorption and hydrogen bonding.

Benefits of technology

It has achieved efficient adsorption of toluene in a low-concentration VOCs environment, with a maximum adsorption capacity of 142 mg/g, an initial adsorption efficiency of up to 98.4%, and good renewable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701893A_ABST
    Figure CN119701893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas adsorption materials, in particular to an MOF-199 derived carbon-montmorillonite composite material as well as a preparation method and application thereof. According to the preparation method of the MOF-199 derived carbon-montmorillonite composite material, MOF-199 and montmorillonite are combined, carbonization and plasma treatment are carried out in sequence to prepare the composite material of porous carbon pillared montmorillonite, and the MOF-199 derived porous carbon can inherit the original advantages of large specific surface area, high porosity and the like of MOF; meanwhile, the electrostatic adsorption interaction between the derivative porous carbon and the methylbenzene can be endowed, hydrophilic functional groups such as carboxyl and hydroxyl on the surface of the material can be increased through plasma treatment, the material and the methylbenzene have a hydrogen-bond interaction, the methylbenzene is firmly trapped in a derivative carbon pillar cage through cooperation of electrostatic adsorption and the hydrogen-bond interaction, and efficient adsorption of the low-concentration methylbenzene is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas adsorption materials, and in particular to a MOF-199 derived carbon@montmorillonite composite material and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) refer to volatile organic compounds with a boiling point below 260°C and a saturated vapor pressure greater than 133.322 Pa at room temperature and pressure. VOCs are widely used in industries such as petrochemicals, semiconductor manufacturing, printing, pharmaceuticals, and paints. They are considered to be one of the main sources of air pollution and cause serious harm to the human body and the environment. VOCs are highly volatile, particularly irritating, toxic and harmful organic gaseous pollutants. Some of them have been listed as carcinogens, such as vinyl chloride, benzene, and polycyclic aromatic hydrocarbons. The harm caused by VOCs to the atmospheric environment is mainly that it promotes the formation of ozone-type photochemical oxidants, causing secondary pollution to the atmospheric environment. When the VOCs in the air reach a certain concentration, people can feel symptoms such as headaches and vomiting, and induce respiratory disorders and respiratory diseases in the human body. In severe cases, it may cause death.

[0003] At present, VOCs end-of-pipe treatment technologies can be divided into two categories. The first category is recycling technology, which mainly includes condensation, absorption, adsorption, and membrane separation. The second category is destruction technology, which mainly includes combustion (including direct combustion, thermal combustion, and catalytic combustion), biodegradation, photocatalytic oxidation, and plasma technology. Among them, the adsorption method is considered to be one of the most promising methods due to its low operating cost, high selectivity and stability, and high removal efficiency.

[0004] Adsorption materials include activated carbon, MOFs, ion exchange resins, zeolites and other materials. Among them, MOFs have attracted widespread attention due to their large specific surface area, designable structure, and multiple active sites. The literature [Ind.Eng.Chem.Res.2023,62,19702-19714] reported a multi-level porous MOF-199@zeolite composite material with high adsorption performance for toluene and acetone. The π-π interaction of MOF-199 on VOCs and the hydrogen bonding effect of zeolite on VOCs are used to achieve synergistic and efficient adsorption. The adsorption capacity for toluene and acetone can reach 505.0 mg / g and 393.3 mg / g, respectively. The document [Environmental Research 184 (2020) 109323] studied the adsorption performance of MOF-199-derived porous carbon for benzene vapor. Using MOF-199 as a precursor, glucose as an additional carbon source, and KOH as an activator, porous carbon was prepared by carbonization at 500°C, and the adsorption capacity for benzene vapor can reach 12.8 mmol / g. Chinese patent CN118162113A discloses a preparation process of a MOF-199-loaded cobalt-impregnated carbon composite material for adsorbing SO2. The initial adsorption efficiency of SO2 reaches 95.1%, and the mass adsorption ratio is 4.56 mg / g. The preparation method is simple and easy to operate, but the mass adsorption ratio effect is not high enough. In summary, MOF materials can effectively adsorb pollutants in high-concentration VOCs environments, but in low-concentration VOCs environments (≤10 ppm), such as chip manufacturing workshops, the adsorption capacity of the above-mentioned MOF materials is limited and cannot achieve effective adsorption and purification. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a MOF-199 derived carbon@montmorillonite composite material and a preparation method and application thereof, so as to at least solve the problem that the existing MOF materials have limited adsorption capacity in a low VOCs concentration environment and cannot effectively adsorb VOCs.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A first aspect of an embodiment of the present invention provides a method for preparing a MOF-199 derived carbon@montmorillonite composite material, comprising the following steps:

[0008] Dissolve copper acetate monohydrate in deionized water, add montmorillonite, disperse by ultrasonic treatment, stir and mix to obtain a metal salt solution; dissolve trimesic acid in a mixed solution containing N, N-dimethylformamide and ethanol, add it dropwise to the metal salt solution at 10-20 mL / min, stir and react at room temperature for 1-2 hours, centrifuge the obtained suspension to obtain a precipitate, wash with ethanol, and obtain MOF-199@montmorillonite;

[0009] The MOF-199@montmorillonite was heated to 450-550°C at a heating rate of 5-10°C / min under an argon atmosphere and calcined for 2-4 hours to obtain a CuO-C@montmorillonite material;

[0010] The CuO-C@montmorillonite was placed in a plasma reactor and treated with plasma using O2 / H2O2 as the working gas to obtain a MOF-199 derived carbon@montmorillonite composite material.

[0011] In combination with the first aspect, in some embodiments, the mass ratio of the copper acetate monohydrate to montmorillonite is 1:(6-9).

[0012] In combination with the first aspect, in some embodiments, the montmorillonite is any one of sodium montmorillonite, calcium montmorillonite, and magnesium montmorillonite.

[0013] In combination with the first aspect, in some embodiments, the mass ratio of the copper acetate monohydrate to trimesic acid is 1:(0.65-0.8).

[0014] In combination with the first aspect, in some embodiments, the mass ratio of trimesic acid, N,N-dimethylformamide and ethanol is (0.65-0.8):(15-20):(13-15).

[0015] In combination with the first aspect, in some embodiments, the suspension is centrifuged at a speed of 5000-6000 r / min for 10-15 min, and then the precipitate is collected.

[0016] In combination with the first aspect, in some embodiments, the conditions of the plasma treatment are as follows: a discharge frequency of 15 to 30 kHz, a discharge voltage of 15 to 20 kV, and a discharge time of 2 to 10 min.

[0017] A second aspect of an embodiment of the present invention provides a MOF-199 derived carbon@montmorillonite composite material, wherein the MOF-199 derived carbon@montmorillonite composite material is prepared by the preparation method described in the first aspect above.

[0018] The third aspect of the embodiments of the present invention provides the use of the MOF-199 derived carbon@montmorillonite composite material described in the second aspect in VOCs adsorption materials.

[0019] In combination with the third aspect, in some embodiments, the MOF-199 derived carbon@montmorillonite composite material is used for VOCs adsorption in a low concentration VOCs environment, wherein the concentration of VOCs in the low concentration VOCs environment is ≤10 ppm.

[0020] In the preparation method of the MOF-199 derived carbon@montmorillonite composite material of the present invention, MOF-199 is combined with montmorillonite, and carbonization and plasma treatment are successively performed to prepare a composite material with porous carbon pillared montmorillonite. The porous carbon derived from MOF-199 can inherit the original advantages of MOF such as large specific surface area and high porosity, and at the same time can give the derived porous carbon an electrostatic adsorption interaction with toluene. The plasma treatment can increase the hydrophilic functional groups such as carboxyl and hydroxyl groups on the surface of the material, which have hydrogen bonding with toluene. The electrostatic adsorption and hydrogen bonding synergistically trap the toluene firmly in the "derivative carbon pillared cage", thereby achieving efficient adsorption of low-concentration toluene.

[0021] The preparation method of the present invention is simple and easy. The prepared MOF-199 derived carbon@montmorillonite composite material has excellent toluene adsorption performance and good regeneration performance. After testing, its maximum toluene adsorption capacity can reach 142 mg / g, and the initial toluene adsorption efficiency is as high as 98.4%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the MOF-199@montmorillonite carbonization and plasma treatment process in the preparation method of the present invention;

[0023] Figure 2 is a toluene adsorption kinetics curve of the MOF-199 derived carbon@montmorillonite composite material prepared in Examples 1-3 and the material prepared in Comparative Examples 1-3;

[0024] Figure 3 It is a toluene adsorption cycle performance diagram of the MOF-199 derived carbon@montmorillonite composite material prepared in Example 3 and the material prepared in Comparative Examples 2-3. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0027] The English letters in the present invention are interpreted as follows:

[0028] DMF: N,N-dimethylformamide.

[0029] Aiming at the problem that in an environment with low VOCs concentration (≤10ppm), such as a chip manufacturing workshop, the adsorption capacity of existing MOF materials is limited and effective adsorption and purification cannot be achieved, the present invention discloses a MOF-199 derived carbon@montmorillonite composite material and a preparation method thereof, wherein MOF-199 is combined with montmorillonite, and carbonization and plasma treatment are successively performed to prepare a composite material with porous carbon pillared montmorillonite, the porous carbon derived from MOF-199 can inherit the original advantages of MOF such as large specific surface area and high porosity, and at the same time can give the derived porous carbon an electrostatic adsorption interaction with toluene, the plasma treatment can increase the hydrophilic functional groups such as carboxyl and hydroxyl groups on the surface of the material, and have hydrogen bonding with toluene, the electrostatic adsorption and hydrogen bonding synergistically trap the toluene firmly in the "derivative carbon pillared cage", and achieve efficient adsorption of low-concentration toluene.

[0030] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of the present invention comprises the following steps:

[0031] Dissolve copper acetate monohydrate in deionized water, add montmorillonite, disperse by ultrasonic treatment, stir and mix to obtain a metal salt solution; dissolve trimesic acid in a mixed solution containing N, N-dimethylformamide and ethanol, add it dropwise to the metal salt solution at 10-20 mL / min, stir and react at room temperature for 1-2 hours, centrifuge the obtained suspension to obtain a precipitate, wash with ethanol, and obtain MOF-199@montmorillonite;

[0032] The MOF-199@montmorillonite was heated to 450-550°C at a heating rate of 5-10°C / min under an argon atmosphere and calcined for 2-4 hours to obtain a CuO-C@montmorillonite material;

[0033] The CuO-C@montmorillonite was placed in a plasma reactor and treated with plasma using O2 / H2O2 as the working gas to obtain a MOF-199 derived carbon@montmorillonite composite material.

[0034] The mass ratio of copper acetate monohydrate to montmorillonite is 1:(6-9), and the montmorillonite is any one of sodium montmorillonite, calcium montmorillonite, and magnesium montmorillonite. The mass ratio of copper acetate monohydrate to trimesic acid is 1:(0.65-0.8), and the mass ratio of trimesic acid, N,N-dimethylformamide, and ethanol is (0.65-0.8):(15-20):(13-15). The suspension is centrifuged at a speed of 5000-6000 r / min for 10-15 minutes, and the precipitate is taken. The conditions for plasma treatment are as follows: the discharge frequency is 15-30 kHz, the discharge voltage is 15-20 kV, and the discharge time is 2-10 minutes.

[0035] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0036] Example 1

[0037] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of this embodiment is as follows:

[0038] (1) Preparation of MOF-199@montmorillonite

[0039] 1 g of copper acetate monohydrate was dissolved in 16 g of deionized water, and then 6 g of sodium montmorillonite was added. The mixture was ultrasonically treated for 30 min to disperse evenly and stirred for 30 min to obtain a metal salt solution. 0.65 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 13 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 1 h to react. The suspension was centrifuged at 5000 r / min for 10 min to obtain a precipitate. The precipitate was washed 5 times with ethanol to obtain MOF-199@montmorillonite.

[0040] (2) Preparation of CuO-C@montmorillonite

[0041] The MOF-199@montmorillonite prepared in step (1) was calcined at 450° C. for 2 h at a heating rate of 5° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite material.

[0042] (3) Plasma treatment

[0043] CuO-C@montmorillonite was placed in a plasma reactor, and O2 / H2O2 was used as the working gas. Under the conditions of discharge frequency of 15kHz, discharge voltage of 15kV and discharge time of 2min, CuO-C@montmorillonite was plasma treated to obtain MOF-199 derived carbon@montmorillonite composite material.

[0044] Example 2

[0045] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of this embodiment is as follows:

[0046] (1) Preparation of MOF-199@montmorillonite

[0047] 1 g of copper acetate monohydrate was dissolved in 18 g of deionized water, and then 9 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.80 g of trimesic acid was dissolved in a mixed solution of 20 g of DMF and 15 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 20 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed 4 times with ethanol to obtain MOF-199@montmorillonite.

[0048] (2) Preparation of CuO-C@montmorillonite

[0049] The MOF-199@montmorillonite prepared in step (1) was calcined at 550° C. for 4 h at a heating rate of 10° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite material.

[0050] (3) Plasma treatment

[0051] CuO-C@montmorillonite was placed in a plasma reactor, and O2 / H2O2 was used as the working gas. Under the conditions of discharge frequency of 30kHz, discharge voltage of 20kV and discharge time of 10min, CuO-C@montmorillonite was plasma treated to obtain MOF-199 derived carbon@montmorillonite composite material.

[0052] Example 3

[0053] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of this embodiment is as follows:

[0054] (1) Preparation of MOF-199@montmorillonite

[0055] 1 g of copper acetate monohydrate was dissolved in 17 g of deionized water, and then 8 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.70 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 14 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed three times with ethanol to obtain MOF-199@montmorillonite.

[0056] (2) Preparation of CuO-C@montmorillonite

[0057] The MOF-199@montmorillonite prepared in step (1) was calcined at 500° C. for 4 h at a heating rate of 10° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite material.

[0058] (3) Plasma treatment

[0059] The CuO-C@montmorillonite was placed in a plasma reactor, and O2 / H2O2 was used as the working gas. Under the conditions of a discharge frequency of 30kHz, a discharge voltage of 20kV, and a discharge time of 5min, the CuO-C@montmorillonite was plasma treated to obtain a MOF-199 derived carbon@montmorillonite composite material.

[0060] Example 4

[0061] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of this embodiment is as follows:

[0062] (1) Preparation of MOF-199@montmorillonite

[0063] 1 g of copper acetate monohydrate was dissolved in 17 g of deionized water, and then 8 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.70 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 14 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed three times with ethanol to obtain MOF-199@montmorillonite.

[0064] (2) Preparation of CuO-C@montmorillonite

[0065] The MOF-199@montmorillonite prepared in step (1) was calcined at 300° C. for 4 h at a heating rate of 10° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite material.

[0066] (3) Plasma treatment

[0067] The CuO-C@montmorillonite was placed in a plasma reactor, and O2 / H2O2 was used as the working gas. Under the conditions of a discharge frequency of 30kHz, a discharge voltage of 20kV, and a discharge time of 5min, the CuO-C@montmorillonite was plasma treated to obtain a MOF-199 derived carbon@montmorillonite composite material.

[0068] Example 5

[0069] The preparation method of the MOF-199 derived carbon@montmorillonite composite material of this embodiment is as follows:

[0070] (1) Preparation of MOF-199@montmorillonite

[0071] 1 g of copper acetate monohydrate was dissolved in 17 g of deionized water, and then 8 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.70 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 14 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed three times with ethanol to obtain MOF-199@montmorillonite.

[0072] (2) Preparation of CuO-C@montmorillonite

[0073] The MOF-199@montmorillonite prepared in step (1) was calcined at 600° C. for 4 h at a heating rate of 10° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite material.

[0074] (3) Plasma treatment

[0075] The CuO-C@montmorillonite was placed in a plasma reactor, and O2 / H2O2 was used as the working gas. Under the conditions of a discharge frequency of 30kHz, a discharge voltage of 20kV, and a discharge time of 5min, the CuO-C@montmorillonite was plasma treated to obtain a MOF-199 derived carbon@montmorillonite composite material.

[0076] Comparative Example 1

[0077] The preparation method of the montmorillonite material of this embodiment is as follows:

[0078] (1) Montmorillonite pretreatment

[0079] Montmorillonite was calcined at 500°C for 4 h at a heating rate of 10°C / min in an argon atmosphere to obtain a montmorillonite material after high-temperature calcination.

[0080] (2) Plasma treatment

[0081] The montmorillonite treated by high temperature calcination is placed in a plasma reactor, and O2 / H2O2 is used as the working gas. Under the conditions of a discharge frequency of 30kHz, a discharge voltage of 20kV, and a discharge time of 5min, the montmorillonite is plasma treated to obtain a plasma-treated montmorillonite material.

[0082] Comparative Example 2

[0083] The preparation method of the composite material of this embodiment is as follows:

[0084] (1) Preparation of MOF-199@montmorillonite

[0085] 1 g of copper acetate monohydrate was dissolved in 17 g of deionized water, and then 8 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.70 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 14 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed three times with ethanol to obtain MOF-199@montmorillonite.

[0086] (2) Plasma treatment

[0087] MOF-199@montmorillonite was placed in a plasma reactor, and MOF-199@montmorillonite was plasma treated with O2 / H2O2 as the working gas under the conditions of a discharge frequency of 30kHz, a discharge voltage of 20kV, and a discharge time of 5min to obtain a plasma-treated MOF-199@montmorillonite composite material.

[0088] Comparative Example 3

[0089] The preparation method of the composite material of this embodiment is as follows:

[0090] (1) Preparation of MOF-199@montmorillonite

[0091] 1 g of copper acetate monohydrate was dissolved in 17 g of deionized water, and then 8 g of calcium montmorillonite was added. The mixture was ultrasonically treated for 60 min to disperse evenly and stirred for 60 min to obtain a metal salt solution. 0.70 g of trimesic acid was dissolved in a mixed solution of 15 g of DMF and 14 g of ethanol, and the mixture was added dropwise to the metal salt solution at a rate of 10 mL / min. The mixture was stirred at room temperature for 2 h, and the suspension was centrifuged at 6000 r / min for 15 min to obtain a precipitate. The precipitate was washed three times with ethanol to obtain MOF-199@montmorillonite.

[0092] (2) Preparation of CuO-C@montmorillonite

[0093] The MOF-199@montmorillonite prepared in step (1) was calcined at 500° C. for 4 h at a heating rate of 10° C. / min under an argon atmosphere to obtain a CuO-C@montmorillonite composite material.

[0094] The toluene adsorption performance of the materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested as follows:

[0095] The final materials prepared in Examples 1-3 and Comparative Examples 1-3 were used as samples for toluene gas adsorption test: The materials were subjected to toluene gas adsorption test using a UTEST static adsorption device. The test flow rate (10 L / min), test resistance (<80 pa), and test concentration (5 ppm) were controlled. The test results are shown in Table 1, and the toluene adsorption kinetic curve is shown in Table 1. Figure 2 , the toluene adsorption cycle performance is shown in Figure 3 .

[0096]

[0097] Table 1

[0098] As can be seen from Table 1, the plasma-treated MOF-199-derived carbon@montmorillonite composites prepared in Examples 1-3 have excellent toluene adsorption performance, and the maximum toluene adsorption capacity can reach 142 mg / g. Comparative Example 1 did not add MOF-199, and the toluene adsorption performance was only 24 mg / g, indicating that the adsorption performance of the montmorillonite material itself was not strong, and the introduction of MOF-199 increased the specific adsorption of toluene by the composite material. Comparative Example 2 did not undergo carbonization treatment, and the adsorption performance decreased, which may be due to the lack of electrostatic adsorption, resulting in performance degradation. Comparative Example 3 did not undergo plasma treatment, and the adsorption performance decreased slightly, indicating that the rich hydrophilic surface functional groups also play an important role in the adsorption of toluene. Combined with Figure 2 It can be seen that the material prepared in Example 3 has the fastest toluene adsorption speed and the largest adsorption capacity, and the adsorption is saturated in about 180 minutes. Figure 3 It shows that after 5 cycles of adsorption, the toluene adsorption capacity of the plasma-treated MOF-199-derived carbon@montmorillonite composite material only decays from the initial 142 mg / g to 135 mg / g, maintaining 95% of the initial toluene adsorption capacity, showing good regenerative performance.

[0099] In summary, the MOF-199 derived carbon@montmorillonite composite material of the present invention can be used in VOCs adsorption materials, especially for VOCs adsorption in low-concentration VOCs environments, where the concentration of VOCs in the low-concentration VOCs environment is ≤10 ppm.

[0100] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A method for preparing a MOF-199 derived carbon@montmorillonite composite material, characterized in that: The following steps are involved: Dissolve copper acetate monohydrate in deionized water, add montmorillonite, disperse by ultrasonic treatment, stir and mix to obtain a metal salt solution; dissolve trimesic acid in a mixed solution containing N, N-dimethylformamide and ethanol, add it dropwise to the metal salt solution at 10-20 mL / min, stir and react at room temperature for 1-2 hours, centrifuge the obtained suspension to obtain a precipitate, wash with ethanol, and obtain MOF-199@montmorillonite; The MOF-199@montmorillonite was heated to 450-550°C at a heating rate of 5-10°C / min under an argon atmosphere and calcined for 2-4 hours to obtain a CuO-C@montmorillonite material; The CuO-C@montmorillonite was placed in a plasma reactor and treated with plasma using O2 / H2O2 as the working gas to obtain a MOF-199 derived carbon@montmorillonite composite material.

2. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 1, characterized in that: The mass ratio of the copper acetate monohydrate to montmorillonite is 1:(6-9).

3. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 2, characterized in that: The montmorillonite is any one of sodium montmorillonite, calcium montmorillonite and magnesium montmorillonite.

4. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 2, characterized in that: The mass ratio of the copper acetate monohydrate to trimesic acid is 1:(0.65-0.8).

5. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 4, characterized in that: The mass ratio of trimesic acid, N,N-dimethylformamide and ethanol is (0.65-0.8):(15-20):(13-15).

6. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 1, characterized in that: The suspension is centrifuged at a speed of 5000-6000 r / min for 10-15 min, and then the precipitate is collected.

7. The method for preparing the MOF-199 derived carbon@montmorillonite composite material according to claim 1, characterized in that: The conditions of the plasma treatment are as follows: the discharge frequency is 15 to 30 kHz, the discharge voltage is 15 to 20 kV, and the discharge time is 2 to 10 min. 8.MOF-199 derived carbon@montmorillonite composite material, characterized in that: The MOF-199 derived carbon@montmorillonite composite material is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the MOF-199 derived carbon@montmorillonite composite material according to claim 8 in VOCs adsorption materials.

10. The use according to claim 9, characterized in that: The MOF-199 derived carbon@montmorillonite composite material is used for VOCs adsorption in a low-concentration VOCs environment, where the concentration of VOCs in the low-concentration VOCs environment is ≤10 ppm.

Citation Information

Patent Citations

  • MOF199 loaded cobalt impregnated carbon composite material as well as preparation method and application thereof

    CN118162113A